RoB 2: a revised tool for assessing risk of bias in randomised trials. (28th August 2019) - Sterne, Jonathan A C; Savović, Jelena; Page, Matthew J; Elbers, Roy G; Blencowe, Natalie S; Boutron, Isabelle; Cates, Christopher J; Cheng, Hung-Yuan; Corbett, Mark S; Eldridge, Sandra M; Emberson, Jonathan R; Hernán, Miguel A; et al.
Abstract : Assessment of risk of bias is regarded as an essential component of a systematic review on the effects of an intervention. The most commonly used tool for randomised trials is the Cochrane risk-of-bias tool. We updated the tool to respond to developments in understanding how bias arises in randomised trials, and to address user feedback on and limitations of the original tool.